Un délire bien fondé - Kamel Chachoua (Revue des Mondes Musulmans et de la Méditerranée, 2018)
This text explores the figure of the “amjah”, the amjah being the immigrant who has broken off from his family and group of origin in Kabylia. It is a figure that is neither rare, nor frequently found in the social and mental environment of the great North African emigration groups. However, it is often absent from sociological and anthropological works and perspective of social and human sciences on emigration-immigration in France. While Kabylian common sense, has always considered “jih” (the fact of being lost in immigration) as a part of the emigrant’s moral and individual degradation, a great deal of these “self disappearances” (jih), are often linked either to intimate conflicts, family’s matrimonial choices or to “honour” disputes in the emigrant’s country of origin. This text deals with the phenomenon of “jih”, beginning with the ritual of “calling” (asiwel), a mainly feminine ritual, which consists in “calling” the lost emigrant (amjah) from the summit of a rock, the top of a tree and the skylight of a mausoleum. If, today, this semi-public open-air calling is not performed anymore or performed exceptionally, it is not due to the fact that people have suddenly assumed its uselessness and aberration, it is because this calling is “intellectualised” and freed from the ceremonial apparatus (tree, rock, mausoleum). It is now performed in petto, in the form of an inward and silent prayer (daawa), with long religious rehearsal learnt from books (the Sourates of the Coran). If the ritual is in decline, it is also because today, emigration is not considered wrong, but as a desired and sought out fate wished by many young people. Finally, this text suggests exploring the new emigration of many single and graduated women, a “solitary” and education-oriented one, a sort of a “disguised” and “distorted” jih. Indeed, the aim of these young women, endowed with strong educational legitimacy and a weaker social legitimacy, is less about accomplishing an emigration project and more about escaping, not to say fleeing a moral and social despotism. Therefore, we can say that a majority of these women conceal their moral emigration behind educational reasons just as some men in the past used to concealing their “moral” emigration (jih) behind working emigration reasons.